2018
DOI: 10.3390/ani8110216
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ‘Selfie’ Tourism on the Behaviour and Welfare of Brown-Throated Three-Toed Sloths

Abstract: Simple SummaryThe use of wild animals as photo props is a potential animal welfare concern that is prevalent across Latin America. The present study documents animal welfare concerns associated with the use of wild caught brown-throated three-toed sloths (Bradypus variegatus) for wildlife ‘selfies’ by tourists at three locations in Manaus, Brazil and Puerto Alegria and Iquitos in Peru. Between 4 October 2016 and 8 April 2017 researchers attended 34 tours, where 17 sloths were observed. The sloths were; (1) hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 42 publications
0
28
0
1
Order By: Relevance
“…For example: “The alligator has about 80 teeth, 40 on top, 40 on the bottom…Their teeth are like a shark’s, they’re always growing, so what you see there is a cap. If they break a teeth off [sic], they’ll grow one right back there in its place” [ 31 ].…”
Section: Qualitative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example: “The alligator has about 80 teeth, 40 on top, 40 on the bottom…Their teeth are like a shark’s, they’re always growing, so what you see there is a cap. If they break a teeth off [sic], they’ll grow one right back there in its place” [ 31 ].…”
Section: Qualitative Resultsmentioning
confidence: 99%
“…Historically, studies addressing the welfare and conservation implications of WTAs have focused on charismatic mammals: e.g., elephants, big cats, and dolphins [30][31][32][33][34][35]. A few studies have examined WTAs involving marine turtles [10,36,37], but other reptiles are rarely addressed in the WTA literature.…”
Section: Introductionmentioning
confidence: 99%
“…One such example of the latter is Carder et al's examination of the use of brown-throated three-toed sloths as 'photo props' at tourist locations in Brazil and Peru (2018). They found that nearly half of the time during which tourists were handling sloths during their photo opportunity was in a way which compromised the sloths' welfare through physically manipulating their body.…”
Section: 'Wild' Selfies and Tourismmentioning
confidence: 99%
“…Carder et al (2018) observed during their study of sloth selfie tourism that other species were available as tourist photo props including "common caiman, green anaconda, and to touch free-ranging baited squirrel monkeys, various parrot species and toucans" (4). Primates The "Disneyfication" of animals through commodified encounters which facilitate wildlife selfie opportunities was recently studied in the context of endangered Barbary Macaques used as photo props in Morocco (Brotcorne et al, 2017;Hsu, Kao, & Agoramoorthy, 2009;Maréchal, Semple, Majolo, & MacLarnon, 2016;Maréchal et al, 2011;Ménard et al, 2014;Stazaker & Mackinnon, 2018).…”
Section: 'Wild' Selfies and Tourismmentioning
confidence: 99%